The Functions of Housing in Response to Changed Lifestyles in Korean Residential Spaces: A Comparative Analysis of the Cases in Lifestyle and Architectural Magazines - Hyun-ah Kwon (MDPI AG, 2021)
The housing type of apartments, spread widely across South Korea, has penetrated deep into its domestic housing culture, thanks to their advantages in terms of convenience, resulting from the mass production of industrial capitalism, which prioritizes functionality and efficiency. However, capitalist social structures have been undergoing transformation in the 21st century. Under a new paradigm emphasizing creativity over functionality and efficiency, the characteristics of everyday life are also changing. We started with the question of apartment spaces, which featured there are only basic minimum functions with simple combinations of similar rooms, without being able to capture the current changed lifestyle. Therefore, this study focuses on newly emerging lifestyles resulting from this transition of social structures and the characteristics of residential spaces at present, centering on the “function of housing”. Based on these considerations, we aimed to establish the essential function of housing that is prioritized by this era. To this end, we first looked at the changes in the functions of housing before and after modern times. We found that the functions of housing that were complex in traditional society have been differentiated and that houses have changed into a more private space along with the post-modern advent of urban public areas. However, the recent shift in social structure has led to the emergence of new lifestyles, which has also called for new functions of housing. Therefore, in this study, through the analysis of recent lifestyle magazines and architectural magazines, we compared the general public’s and architectural experts’ perspectives on the changed functions of housing and the characteristics of the required residential space. Accordingly, this research analyzed articles containing interviews with residents in lifestyle magazines and articles of architects and critics in architectural magazines. In addition to our previous literatures on changes in “characteristics of residents” and “relationship between individual and family”, this study will ignite discussions on contemporary urban housing from diverse and multi-layered levels as an attempt to achieve sustainable housing where residents’ everyday lives and their residential spaces match.